Between the anthropic and the natural heritage: The relationship of the residents of the Bode community with the Parque dos Manguezais, Recife-PE. - Moura, Célio Henrique Rocha; Albuquerque, Caio Coelho Silva; Araujo, Felipe Moura Hemetério (National Journal of City Management, 2021)
This investigation is inserted on the nature conservation heritage cover, starting from the comprehension of an intrinsic relation between ecosystems and dependent communities, this article covers the Parque dos Manguezais, A Conservation unit of Recife city and the Bode community, historically related to the ecosystem. From this relation flourishes fisher activities developed by inhabitants since the XVII century, at the first territorial occupations, shaping the natural territory, until the contemporaneity, when real estate market pressure imposes to these residents a slowly but continuous process of gentrification. Hence, the research pointed out the relations of the residents with the Parque dos Manguezais, identifying how fishing is converted on an element that defines culture and the local social dynamic, being an essential fact to be considered to the anthropic and natural management to grant the community survival that coexists with the nature and historically manages its natural resources.